2001
DOI: 10.1176/appi.ps.52.9.1248
|View full text |Cite
|
Sign up to set email alerts
|

Refill Patterns of Atypical and Conventional Antipsychotic Medications at a National Retail Pharmacy Chain

Abstract: This study examined whether patients who received prescriptions for conventional and atypical antipsychotics in routine outpatient care continued medication therapy. Prescription refill records of more than 25,000 patients from a national retail pharmacy chain were surveyed during a full eight-month period. At the start of the ninth month, 48 percent of the patients taking conventional agents were continuing therapy. The overall rate for those taking atypical agents was 44 percent; however, the rate for those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…Antipsychotic medication is a critical component of the successful treatment for schizophrenia, yet nonadherence to these medications continues to be a major problem for 40-50% of patients with schizophrenia [148]. The results of current research are mixed regarding rates of adherence to the newer antipsychotic medications [141,[149][150][151][152][153].…”
Section: Discussionmentioning
confidence: 99%
“…Antipsychotic medication is a critical component of the successful treatment for schizophrenia, yet nonadherence to these medications continues to be a major problem for 40-50% of patients with schizophrenia [148]. The results of current research are mixed regarding rates of adherence to the newer antipsychotic medications [141,[149][150][151][152][153].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this evidence, research on outpatient utilization spanning 1987−1997 shows that it rarely is continuous in a given year (dosReis et al 2002;McCombs et al 1999;Menzin et al 2003;Mojtabai et al 2002;Vanelli et al 2001;Velligan et al 2003;Williams et al 1999). Only 12−30% of individuals received continuous antipsychotic treatment over a one year period (McCombs et al 1999;Williams et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…From 17−24% of adults with schizophrenia do not receive medication in outpatient settings (dosReis et al 2002;McCombs et al 1999). Prescription refills over a nine-month period in 1998−1999 indicate that approximately 30% of individuals discontinue antipsychotic medication within three months after initiating treatment (Vanelli et al 2001). Following hospital discharge, 37% of adults with schizophrenia discontinue medication within one month (Mojtabai et al 2002), rising to 60% at three months (Velligan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While some studies show a significant superiority in adherence rates with AAs, others show little advantage or inconclusive results Lacro, Dunn, Dolder, Leckband, & Jeste, 2002;Rosenheck et al, 2003;Vanelli, Burstein, & Crammer, 2001). Depending on the study design, measurement methods, and success criteria, reported rates of nonadherence to antipsychotic medication range from 11 to 80%, with an average rate of 50% (Dolder, Lacro, & Jeste, 2003;Lacro et al, 2002;Weiden & Olfson, 1995).…”
Section: Introductionmentioning
confidence: 99%